GREEN MARKETING STRATEGY IN ATTRACTING CONSUMERS WHO CARE ABOUT THE ENVIRONMENT - Johni Eka Putra; Andriya Risdwiyanto; Riantin Hikmah Widi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The growing desire of customers for environmentally friendly products means companies are competing to meet these needs by switching to using environmentally friendly materials. The materials in question are not only raw materials but also involve other materials such as product packaging, labeling, packaging and so on. Environmental awareness by implementing green marketing strategies can be done with environmentally friendly promotions. The growing desire of customers for environmentally friendly products means companies are competing to meet these needs by switching to using environmentally friendly materials. Green marketing is an approach to marketing that emphasizes environmental and sustainability values. It aims to attract consumers who care about environmental issues and promote environmentally friendly products or services. Several green marketing strategies that can be used to attract consumers who care about the environment are sustainable communication, labels and certification, transparency, customer education, partnerships with environmental organizations, focusing on environmental innovation, and sustainable consumer support.